2007
DOI: 10.1093/ajcn/86.4.1104
|View full text |Cite
|
Sign up to set email alerts
|

Milk consumption during pregnancy is associated with increased infant size at birth: prospective cohort study

Abstract: Milk intake in pregnancy was associated with higher birth weight for gestational age, lower risk of SGA, and higher risk of LGA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
169
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(183 citation statements)
references
References 31 publications
12
169
2
Order By: Relevance
“…Mannion et al (2006) found that intake of milk fortified with vitamin D, and intake of vitamin D were each positively associated with birthweight. Olsen et al (2007) also found that milk and milk protein intake was associated with higher birthweight and suggested that water soluble substances in milk increase fetal growth. They did not investigate vitamin D intake.…”
Section: Discussionmentioning
confidence: 92%
“…Mannion et al (2006) found that intake of milk fortified with vitamin D, and intake of vitamin D were each positively associated with birthweight. Olsen et al (2007) also found that milk and milk protein intake was associated with higher birthweight and suggested that water soluble substances in milk increase fetal growth. They did not investigate vitamin D intake.…”
Section: Discussionmentioning
confidence: 92%
“…Knudsen et al found that women with a 'health conscious' dietary pattern characterized by higher intake of fruits and vegetables, fish and poultry had 24 % reduced odds of delivering an SGA infant compared with women with a 'Western' dietary pattern characterized by a higher intakes of red and processed meat, high-fat dairy and energy (36) . Olsen et al demonstrated reduced odds of SGA with increasing maternal milk consumption as compared with no milk intake, as well as higher odds of LGA with milk intakes exceeding 2-3 glasses/d (37) . Brantsaeter et al found reduced risk of SGA but no impact on risk of LGA with higher fish and seafood intake (38) .…”
Section: Discussionmentioning
confidence: 99%
“…Milk contains many potentially growth-promoting factors and is associated with higher birth weight for gestational age (Olsen et al, 2007). Furthermore, a study in a group of pregnant African-American adolescents found that nutrition was significantly related to fetal femur growth during pregnancy, such that dairy intakes of o2 servings per day were associated with lower fetal bone development than were greater intakes of dairy (Chang et al, 2003).…”
Section: Discussionmentioning
confidence: 99%